EFEKTIFITAS PEMBERIAN JUS TOMAT DAN JUS JERUK TERHADAP PENINGKATAN KADAR HEMOGLOBIN PADA IBU HAMIL DENGAN ANEMIA - Sulung, Neila (REAL in Nursing Journal, 2018)
Anemia in pregnancy is a condition to a decrease in hemoglobin. Most of anemia is iron deficiency anemia (Fe) which can be caused by the consumption of iron that is less than the food. The prevalence of anemia at Public Health Center Nilam Sari Bukittinggi are 39.5%. The aims of this study was to determine the effectiveness of tomato juice and orange juice to increase hemoglobin levels in pregnant women with the quasi experiment study design using two group pretest postetst. Research has been conducted at Public with 20 sample by using purposive sampling technic. Test conducted with T-Test Dependent. Results of the study group I showed an average increase in hemoglobin levels of pregnant women before and after the intervention of 1.17. Statistical test result p value=0.004 (p<0.05), we conclude tomato juice at effectively increase hemoglobin levels of pregnant women. The second group also showed an increase in hemoglobin levels of pregnant women before and after the intervention of 0.63. Statistical test result p value=0.001 (p<0.05), conclude orange juice effectively increase hemoglobin levels of pregnant women. Tomato juice and orange effective  to increase hemoglobin levels to pregnant women with anemia. It is expected that the health clinic to provide health education on complementer therapies that can help increase hemoglobin levels in pregnant women, one of which is a combination therapy of tomato juice or orange juice.Keywords: tomato juice, orange Juice, pregnant women, hemoglobin